The Diversity of Makrozoobenthos as Bio-Indicators of Water Quality of the River Kundur District Labuhanbatu - Winarti Winarti; Arman Harahap (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Macrozoobenthos used as a bioindicator of the waters, this happens because of the nature of the benthos which has mpergerakan low so it got a lot of influence from the environment. This study aims to determine the condition of the river Kundur with a view the community structure of macrozoobenthos which include: species composition, abundance, diversity, uniformity and dominance as well as the physical and chemical parameters of water as a paremeter supporters. Based on the results of observations, macrozoobenthos were found during the study in the river Kundur consists of 3 phylum, 4 classes, 17 family with 11 species. The composition of the class of macrozoobenthos in the whole of the observation station consists of a Gastropod (37%), Insecta (23%), Malacostraca (20%), Polychaeta (10%) dan Malacostraca (20%). The value of an abundance ranged from 325,7 - 3309,6 ind/m3. With the value of the total abundance at Station I which is equal to 3690,1 ind/m3, Station II 3723,1 ind/m3, Station III 3692,3 ind/m3 can be categorized diversity are light polluted with the value of the index of uniformity (E) that describes the spread of the individual tends to be uniform or relatively the same. While the condition of the physical-chemical parameters and the substrate bottom of the river Kundur in general has a range of relatively homogeneous, spread evenly throughout the observation stations and still be able to support life macrozoobenthos. To the results of measurements of the parameters of physico-chemical water and substrate in the river kundur in general has a range of relatively homogeneous in the whole observation stations and still be able to support the life of the macrozoobenthos.